Peran Program Habituasi Nilai Pancawaluya Dalam Mewujudkan Sekolah Berkarakter Di Sman 1 Ligung - Harianto, Eka; Cahyani, Dewi; Ali, Moh. (Universitas Pakuan, 2025)
THE ROLE OF THE PANCAWALUYA VALUE HABITUATION PROGRAM IN CREATING A CHARACTER-BASED SCHOOL AT SMAN 1 LIGUNGCharacter education is an important foundation in the formation of a generation with good morals, intelligence, and responsibility. SMAN 1 Ligung through the Pancawaluya Values Habituation Program (Cageur, Bageur, Bener, Pinter, and Singer) strives to instill moral, social, and spiritual values that are integrated into all school activities. This study aims to analyze the role and implementation of the Pancawaluya values habituation program in realizing a character-based school with a religious values-based educational management approach. The method used is descriptive qualitative through observation, interviews, and documentation. The results show that the application of Pancawaluya values is able to form a school culture that is religious, disciplined, socially concerned, and oriented towards improving the quality of learning. Educational management at SMAN 1 Ligung plays an important role in the planning, implementation, and evaluation of the habituation program through cross-sector coordination, strengthening teacher capacity, and habituating religious and social activities. Religious values are the main foundation in the internalization of Pancawaluya values so that students are physically and mentally healthy, have noble morals, and have strong characters.